2014
DOI: 10.1002/jhbp.185
|View full text |Cite
|
Sign up to set email alerts
|

Tips in biliary stone removal using endoscopic papillary large balloon dilation

Abstract: The use of limited endoscopic sphincterotomy with large balloon dilation (ESLBD) has recently been shown to be useful for removal of large common bile duct stones in a dilated bile duct. The technique can reduce the need of mechanical lithotripsy, risk of adverse events and costs of the procedure. The aim of the review is to provide an overview in the current status of ESLBD with particular focus on the technical aspects of the technique for bile duct stone removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thus, there is presently no clear evidence regarding the incidence of procedural events and balloon diameter. In reference to an expert opinion based on animal experiments, it has been suggested that the use of a balloon ≥15 mm in diameter should be avoided as much as possible as it increases the risk of perforation . However, many experts advocate selecting a balloon diameter that does not exceed the range of the bile duct diameter and the short diameter of the stone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is presently no clear evidence regarding the incidence of procedural events and balloon diameter. In reference to an expert opinion based on animal experiments, it has been suggested that the use of a balloon ≥15 mm in diameter should be avoided as much as possible as it increases the risk of perforation . However, many experts advocate selecting a balloon diameter that does not exceed the range of the bile duct diameter and the short diameter of the stone.…”
Section: Methodsmentioning
confidence: 99%
“…In reference to an expert opinion based on animal experiments, it has been suggested that the use of a balloon ≥15 mm in diameter should be avoided as much as possible as it increases the risk of perforation. 45 However, many experts [46][47][48] advocate selecting a balloon diameter that does not exceed the range of the bile duct diameter and the short diameter of the stone. Regarding the measurement of the bile duct diameter, the distal bile duct is narrow in some patients 46 and therefore the diameter of the distal bile duct should be measured.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated adverse events including pancreatitis, bleeding, and perforation are caused by excessively high balloon pressure. [1][2][3][4][5] Therefore, we devised a new technique for EPLBD to avoid high balloon pressure.…”
mentioning
confidence: 99%
“…Endoscopic papillary large balloon dilation (EPLBD) has been recently introduced to remove large common bile duct stones (CBDSs). The associated adverse events including pancreatitis, bleeding, and perforation are caused by excessively high balloon pressure 1–5 . Therefore, we devised a new technique for EPLBD to avoid high balloon pressure.…”
mentioning
confidence: 99%